Opportunities and challenges for synthetic biology in the therapy of inflammatory bowel disease - Dong, Yumeng; Xu, Tiangang; Xiao, Guozheng; Hu, Ziyan; Chen, Jingyu (Frontiers in Bioengineering and Biotechnology, 2022)
Inflammatory bowel disease (IBD) is a complex chronic intestinal inflammatory disorder that primarily includes Crohn's disease (CD) and ulcerative colitis (UC). Although traditional antibiotics and immunosuppressants are known as the most effective and commonly used treatments, some limitations may be expected, such as limited efficacy in a small number of patients and gut flora disruption. Great many research has been done with respect to the etiology of IBD, while the composition of the gut microbiota is suggested as one of the most influential factors. Along with the development of synthetic biology and the continuing clarification of IBD etiology, broader prospects for novel approaches to IBD therapy could be obtained. This study presents an overview of currently existing treatment options and possible therapeutic targets at the preclinical stage with respect to microbial synthesis technology in biological therapy. This study is highly correlated to the following topics: microbiota-derived metabolites, microRNAs, cell therapy, calreticulin, live biotherapeutic products (LBP), fecal microbiota transplant (FMT), bacteriophages, engineered bacteria, and their functional secreted synthetic products for IBD medical implementation. Considering microorganisms as the main therapeutic component, as a result, the related clinical trial stability, effectiveness, and safety analysis may be the major challenges for upcoming research. This article strives to provide pharmaceutical researchers and developers with the most up-to-date information for adjuvant medicinal therapies based on synthetic biology.